Right-Wing Extremism and Terrorism with Roots In (Neo)Colonization - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2024)
Many Western countries and their citizens react to right-wing extremism as if it were a coup against the democratic rule of law. This article explores the reasons for this. It does so as follows. First, by outlining what is meant by right-wing extremism. But also by addressing the theories that right-wing extremists use to support their ideology of destruction and subversion. Second, this article examines the numbers of right-wing extremists in Europe and in the European Parliament. In this European Parliament, right-wing extremists have become a party that cannot be ignored. In fact, even Hungary's far-right prime minister, Viktor Orbán, is now taking over the EU presidency for six months. Third, this article addresses the threat of right-wing extremist terrorism. This is done on the basis of a number of states that oppress citizens in their own and neighboring countries, invoking the adage: "one's own country and one's own people come first. Russia and Israel are the two countries most often mentioned. Attention is also paid to individual Western far-right terrorists who target Muslims, sub-Saharan Africans, and the "leftist" elite. Their far-right ideology is strongly discussed in this article. Fourth, we test the hypothesis that the ancestors of right-wing extremists had their first experiences with dismissing the other as inferior and inferior in the former Western colonies. In doing so, we do not close our eyes to neocolonial behavior. The elaboration of this hypothesis is that they treat immigrants, refugees and expatriates in the same way as their ancestors did in the former colonies on the African, Asian and American continents. Isolation, exploitation, enslavement, plundering, looting and torture, as well as genocidal wars, were the order of the day. Epigenetics shows that the distinction between genotype and phenotype is based on genotypic changes due to phenotypic conditions. In short, poor living conditions due to institutional racism, stress, pollution, overcrowding and deprivation lead to negative genetic changes. The victims of epigenetic transformation are mainly immigrants, refugees and expatriates in Western countries and the original populations in the former Western colonies. Finally, this article shows that it is a significant number of immigrants, refugees, and expatriates who are told by right-wing extremists that they are not welcome in their continent, country, province, neighborhood, and street. With God's evidence, this article shows that human beings were not created to fight each other with fire and sword.